2006
DOI: 10.1002/bjs.5289
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative touch imprint cytology for the diagnosis of sentinel lymph node metastases in breast cancer

Abstract: TIC is feasible and enables the rapid diagnosis of SLN metastases with an acceptable accuracy for clinical use in ductal carcinoma of the breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…25,26 Both of these studies concluded that the sensitivity of TIC was better for detecting macrometastases than micrometastasis. 25,26 A small study of 17 patients demonstrated that TIC was accurate in patients who had received preoperative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Both of these studies concluded that the sensitivity of TIC was better for detecting macrometastases than micrometastasis. 25,26 A small study of 17 patients demonstrated that TIC was accurate in patients who had received preoperative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Both of these studies concluded that the sensitivity of TIC was better for detecting macrometastases than micrometastasis. 25,26 A small study of 17 patients demonstrated that TIC was accurate in patients who had received preoperative chemotherapy. 27 Importantly, this study identified distinct TIC cytologic patterns in those patients treated with preoperative chemotherapy, which may confound accurate slide interpretation in this patient subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…6 Reported sensitivity of TIC varies from 33.3 to 100%. [14][15][16] Overall sensitivity and specificity of TIC in the present study based on the number of the patients was 66.7% and 98.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our TIC accuracy was consistent with other studies. 6,17 Sensitivity of TIC in our practice may be affected by preselection of gross node-positive patients by axillary ultrasound. In these situations, we normally proceed with ALND directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation